KOORDINASI PEMERINTAH DALAM PERCEPATAN PENANGGULANGAN KEMISKINAN EKSTREM DI KABUPATEN SIAK TAHUN 2022-2023 - ,, Sulistiawati; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Extreme poverty is a condition where a person cannot meet their basic needs. This poverty problem is a complex issue that requires cooperation and coordination. Coordination teams were formed to improve coordination in the field of regional poverty alleviation, namely the Provincial TKPK and the Regency TKPK. The Siak Regency Government established a Poverty Alleviation Coordination Team which carries out the function of coordinating the regional government in accelerating extreme poverty alleviation. The problem in this study is the decrease in the number of extreme poverty in Siak Regency from 2022 to 2023, namely from 6.42 thousand people or 1.27% to 2.79 thousand people or 0.54%. In addition, this acceleration of poverty alleviation still faces several challenges, especially in terms of coordination. The purpose of this study is to determine government coordination in accelerating extreme poverty alleviation in Siak Regency in 2022-2023. The theory used in this study is the coordination theory. The research approach used was qualitative. The type of research employed was descriptive research. The research location was in Siak Regency. The data types were primary and secondary. Primary data was obtained directly from informants, while secondary data was supporting data in the form of documents related to the research problem. Data collection techniques included interviews and documentation. Data analysis was conducted using qualitative analysis. The results of this study are that government coordination carried out by the Poverty Alleviation Coordination Team of Siak Regency has been running quite well by implementing unity of action, communication, division of labor and discipline. However, from several indicators, shortcomings are still found, such as in terms of communication where there are still many TKPK members who only attend meetings if their agency is involved, in terms of division of labor, there are still more assistance given than empowerment and in terms of discipline it cannot be said to be optimal, this is because the TKPK does not have written standard operating procedures, so from these shortcomings it is hoped that the TKPK can improve it so that in the future it can really accelerate the reduction of extreme poverty in Siak Regency. Keywords: Government Coordination, Poverty, Extreme Poverty, TKPK